Organic light-emitting devices based on solution-processable small molecular emissive layers doped with interface-engineering additives. Issue 39 (5th April 2016) - Ha, Tae-Won; Kim, Young-Baek; Heo, Gi-Seok; Hwang, Inchan; Jeon, Hong Goo; Park, Byoungchoo
Abstract : A simple solution-process to fabricate full-colour small molecular OLEDs is proposed. The incidence of nano-pinhole defects decreases sharply following the introduction of an interface-engineering additive, resulting in good device performance. Abstract : In this study, we investigate small molecular organic light-emitting diodes (SM-OLEDs) consisting of emission layers (EMLs) fabricated using a solution-coating process of self-metered horizontal dip- (H-dip-) coating. The EML used was composed of a co-mixed small molecular host matrix of hole-transporting 4, 4′, 4′′-tris(9-carbazolyl)-triphenylamine (TcTa) and electron-transporting 2, 7-bis (diphenyl phosphoryl)-9, 9′-spirobifluorene (SPPO13) doped with blue-, green-, and/or red-emitting phosphorescent iridium complexes. To improve the electron-injecting and hole-blocking properties at the cathode interface and to enhance the film-forming capabilities, an interface-engineering additive of poly(oxyethylene tridecyl ether) (PTE) was mixed with the small molecular EMLs. Using PTE additives was shown to reduce dramatically the formation of film defects such as nano-pinholes in the EMLs, resulting in thin and homogeneous PTE-mixed EMLs with smooth surface morphologies, even when using a single H-dip-coating process. The use of simple H-dip-coated EMLs mixed with PTEs in SM-OLEDs resulted in good device performance, with maximum luminance levels of 29 200 cd m −2, 115 000 cd m −2, and 16 400 cd m −2, with corresponding peak current efficiencies of 18.8 cd A −1, 31.2 cd A −1, and 10.0 cd A −1, for blue, green, and red SM-OLEDs, respectively. Furthermore, we demonstrated the feasibility of fabricating large-area and high-performance solution-processable SM-OLEDs using H-dip-coated EMLs doped with PTEs. These results clearly indicate that H-dip-coated small molecular EMLs mixed with PTE can be used to yield simple, bright, and efficient solution-processable SM-OLEDs.